Problematika Guru Bahasa Inggris dalam Penerapan Kurikulum Merdeka Belajar di SD Negeri 067090 Medan - Deasy Yunita Siregar; Aisyah Rizqa Fitri Siregar; Anggi Rahmanida Nst; Rahma Fitri Yani Lubis; Rahmi Rahmita Tanjung (Simpati, 2024)
This type of research is descriptive qualitative, with the aim of finding out the implementation of the independent curriculum at SD Negeri 067090 Medan, as well as the problems of English teachers in implementing the independent curriculum at SD Negeri 067090 Medan. Data collection techniques were carried out using interview, observation and documentation methods. The independent curriculum is an update that is motivated by increasingly advanced technology nowadays, and is also prepared as a strategy to mitigate the learning crisis due to the Covid-19 pandemic. Apart from that, this curriculum also aims to provide freedom to both institutions and teachers in developing and managing curriculum and learning that is adapted to the characteristics of the educational unit and students so that they can explore their talents. Many schools have started implementing the independent curriculum in this new academic year. Therefore, various elements of education are required to adapt to this. From the research results, it can be seen that the problem of English teachers at SD Negeri 067090 Medan, namely that English teachers still do not understand the concept of an independent curriculum, teachers are faced with obstacles in creating teaching and planning modules, learning planning, namely when analyzing learning outcomes, preparing the flow. learning objectives that are adjusted to students' abilities, 3) solutions carried out by Islamic religious education teachers to overcome problems in the independent curriculum, namely English teachers taking part in in-house training and training held by the school and education department, attending KKG meetings held once a month very.